Sleep-Disordered Breathing and Associated Comorbidities among Preschool-Aged Children with Down Syndrome - Tessa K. Kolstad; Lourdes M. DelRosso; Mary Anne Tablizo; Manisha Witmans; Yeilim Cho; Michelle Sobremonte-King (MDPI AG, 2024)
Children with Down syndrome (DS) are at high risk of sleep-disordered breathing (SDB). The American Academy of Pediatrics recommends a polysomnogram (PSG) in children with DS prior to the age of 4. This retrospective study examined the frequency of SDB, gas exchange abnormalities, co-morbidities, and surgical management in children with DS aged 2-4 years old at Seattle Children's Hospital from 2015-2021. A total of 153 children underwent PSG, with 75 meeting the inclusion criteria. The mean age was 3.03 years (SD 0.805), 56% were male, and 54.7% were Caucasian. Comorbidities included (n, %): cardiac (43, 57.3%), dysphagia or aspiration (24, 32.0%), prematurity (17, 22.7%), pulmonary (16, 21.3%), immune dysfunction (2, 2.7%), and hypothyroidism (23, 30.7%). PSG parameter data collected included (mean, SD): obstructive AHI (7.9, 9.4) and central AHI (2.4, 2.4). In total, 94.7% met the criteria for pediatric OSA, 9.5% met the criteria for central apnea, and 9.5% met the criteria for hypoventilation. Only one child met the criteria for hypoxemia. Overall, 60% had surgical intervention, with 88.9% of these being adenotonsillectomy. There was no statistically significant difference in the frequency of OSA at different ages. Children aged 2-4 years with DS have a high frequency of OSA. The most commonly encountered co-morbidities were cardiac and swallowing dysfunction. Among those with OSA, more than half underwent surgical intervention, with improvements in their obstructive apnea hypopnea index, total apnea hypopnea index, oxygen saturation nadir, oxygen desaturation index, total arousal index, and total sleep duration. This highlights the importance of early diagnosis and appropriate treatment. Our study also suggests that adenotonsillar hypertrophy is still a large contributor to upper airway obstruction in this age group.